Numerical simulation of DBD plasma actuators for flow control - Borradaile, Huw (2021)
Millimetric and sub-millimetric DBD plasma actuators have been investigated for flow control applications using a 4-species plasma-fluid model. The discharge structures for a number of cases were studied and an understanding of the mechanics of these plasma actuators was developed.